Realization of inhomogeneous magnetic field for prism-type mass analyzer - P.O. Kuzema; O.S. Kuzema (Журнал нано- та електронної фізики)
The configuration of magnet polar tips, which form in its gap the inhomogeneous magnetic field with the axial symmetry, has been determined and the technology of their production has been described. It is shown that for the given value of the polar tip apex angle, the necessary heterogeneity of magnetic field can be provided by the corresponding choice of the interpolar gap width of the mass analyzer magnet.